2021
DOI: 10.1103/physreve.103.023303
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the throat size distribution of a porous medium as an inverse optimization problem combining pore network modeling and genetic and hill climbing algorithms

Abstract: The pore size distribution of a porous medium is often estimated from the retention curve or the invading fluid flow rate curve using simple relationships more or less explicitly based on the consideration that the porous medium is made of a bundle of cylindrical parallel tubes. This type of determination is tested using pore network simulations. Starting from two-or three-dimensional networks, the characteristics of which are known apriori, the estimation of the throat size distribution (TSD) is performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 33 publications
0
40
0
Order By: Relevance
“…As considered in Ref. [29] in the case of the throat size distribution (TSD) determination problem, it is possible to perform the optimization procedure considering only one datum, either the capillary-pressure curve or the relative permeability curve. For the TSD problem, it was found that considering both data led to the best results and that the consideration of the capillary-pressure curve alone led to better results than the relative permeability curve alone.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As considered in Ref. [29] in the case of the throat size distribution (TSD) determination problem, it is possible to perform the optimization procedure considering only one datum, either the capillary-pressure curve or the relative permeability curve. For the TSD problem, it was found that considering both data led to the best results and that the consideration of the capillary-pressure curve alone led to better results than the relative permeability curve alone.…”
Section: Discussionmentioning
confidence: 99%
“…The capillary-pressure curve P c (S), where S is the saturation of the displaced fluid, is computed using an algorithm similar to the one presented in Refs. [29,39], but takes into account here the presence of hydrophilic elements. This algorithm mimics the commonly used experimental procedure [25].…”
Section: B Capillary-pressure Curve Computationmentioning
confidence: 99%
See 3 more Smart Citations